Willingness to Pay for Biofortified Rice in Cartagena, Colombia - Oswalt, Sara; Rivera Vasco, Tatiana Carolina; Nasner Tacan, Hans; Durant-Morat, Alvaro; Gallego Castillo, Sonia; Andrade López, Robert Santiago (2024)
This data set contains the prices offered under experimental conditions by 400 participants for a pound of three types of rice (regular, premium, and biofortified) in the Cartagena municipality in Colombia—furthermore, a brief socio-economic characterization of the participants and their nutrition knowledge. Metodology:Experimental Auction with three rounds varying the participants' level of information regarding the rice they were testing. In the case of the characterization in-person one-to-one survey.